Thermodynamic behavior and polymorphism of 1-butyl-3-methylimidazolium hexafluorophosphate composites with multiwalled carbon nanotubes - Liavitskaya, Tatsiana (J Chem Thermodyn, 2019)
Based on room-temperature densities measured in this research for ionic nanofluids (INFs) with four ionic liquids (ILs), we conclude that evacuation is a necessary step to maximize the IL penetration into multiwalled carbon nanotubes (MWCNT). An improved procedure for reproducible preparation of INFs is proposed. Thermal behavior of five (1-butyl-3-methylimidazolium hexafluorophosphate + MWCNT) samples was studied by adiabatic calorimetry over the temperature range (78 to 370) K. The samples contained from 0.11 to 0.92 mass fraction of the nanophase. Their appearance changed from the fluid to the powder with increasing the MWCNT content. For the fluid samples, the specific heat capacity was found be an additive quantity of the specific heat capacities of the components for the crystal and liquid phases, and the temperatures of phase transitions did not change relative to the bulk values. For the powder-like sample with the highest IL content, a sigmoidal heat capacity curve was observed. Thus, the internal diameter of the studied MWCNT was small enough to switch from the isothermal melting process to the gradual transition from the crystal-like structures to the liquid-like ones.